THE METHODS FOR KNOWLEDGE MANAGEMENT IN INDUSTRIAL SECTOR: A CASE STUDY OF INDUSTRIAL ESTATES THROUGHOUT THAILAND - จารุธีรศานต์ ปิยะฉัตร (RMUTT Global Business and Economics Review, 2015)
The objectives of this research are 1) to investigate a suitable knowledge management method for factories in industrial estates throughout Thailand, 2) to study a general situation of knowledge management in organizations including problems and obstacles of knowledge management for factories in industrial estates throughout Thailand, and 3) to study factors affecting to knowledge management methods or tools and problems and obstacles of knowledge management development. The sample of study was consisted of top and intermediate levels of executives and knowledge-management managers who were currently active in knowledge management tasks from the successful top-listed factories of 290 factories. Two persons of each factory were carefully chosen from top-to-intermediate levels of executives and knowledge-management managers having the total respondents of 580 people. Questionnaires were used as a tool for data collection. Statistical analyses in this research were analysis of variance (ANOVA) and LSD for comparison of differences of data in pairs. From the results, it was found that most of the factories have used human resource developments as a part of knowledge management method. Most of the factories have done knowledge management for 1-5 years aiming for human-resource development and official arrangement for knowledge management activities. Also, most of the factories had problems and obstacles on knowledge-management developments in intermediate levels, i.e., top-level executives have not continuously supported or not participated in knowledge-management. Results of ANOVA were shown that the knowledge management method was not significantly different for different sizes of factories and understandings of executives in knowledge management in industrial sector.